A Case of Heart Failure due to Triple Vessel Coronary Artery Disease: Role of General Practitioner - Muslimin Budiman Satryanto; Sidhi Laksono (Universitas Muhammadiyah Malang, 2022)
Heart failure with reduced ejection fraction (HFrEF) is a complex clinical syndrome characterized by a left ventricular ejection fraction ≤ of 40%. Primarily the etiology of heart failure is due to coronary artery disease (CAD). Patients with multivessel disease are considered for revascularization procedures with coronary artery bypass grafting (CABG). We report patient with HFrEF due to three-vessel disease (3VD) is not indicated for revascularization and only gets a conservative therapy to improve the patient's quality of life. A 52-year-old man visited the cardiologist to get control his condition. The patient experienced shortness of breath, heartburn, cold sweat, and fatigue. The physical and blood examination was normal, electrocardiography showed fragmented QRS complex, V1-V3 poor R waves progression, and V5-V6 T waves inverted. The echocardiography showed a result of ejection fraction is only 30%. He was treated with acetylsalicylic acid, bisoprolol, valsartan, furosemide, nitroglycerin, spironolactone, and isosorbide dinitrate. Treatment with CABG was not carried out. The ejection fraction was raised to 40% and he was clinically improved. HFrEF due to CAD3VD could be treated with fully conservative therapy and not indicated for revascularization treatment because of coronary anatomy and myocardial viability. A comprehensive approach should be evaluated by Heart Team.